DESCRIPTION OF THE LEVEL OF KNOWLEDGE ABOUT HEALTHY SNACK FOODS IN STATE ELEMENTARY SDN 106172 - Faradillah; Alfareza, Alditia; Hasibuan, Syahrida Suryani; Lubis, Fatma Sri Ramadhan (International Archives of Medical Sciences and Public Health, 2025)
Healthy snacks are light meals or snacks that have good nutritional value and provide many benefits to health. Healthy snacks generally contain important nutrients such as vitamins, minerals, fiber, protein, and healthy fats. Therefore, snack foods are also a matter that needs attention from the public, as there are some snack foods that are unhygienic and pose a significant risk of contamination that can affect health. This is particularly important for elementary school children who are very vulnerable to this issue because they do not yet understand how to choose healthy snacks, which can have negative effects on their own health (Suci, 2009). This counseling aims to assess the knowledge of students at SD Negeri 106172 Tuntungan regarding healthy snacks and the benefits that can be obtained from consuming such foods. The method used in this research is a quantitative descriptive design method that involves three stages: pre-test, providing material through counseling and role-playing with the students, and post-test. The total number of respondents in this study was 30 people aged between 10-12 years old. The results of this study show that the level of knowledge about healthy snacks for students at SD Negeri 106172 Tuntungan falls into the category of "sufficient." However, after being provided with material about healthy snacks, their knowledge improved and reached the "good" category. The knowledge level of students at SD Negeri 106172 Tuntungan regarding healthy snacks during the pre-test was 74.6%, and after providing the material, conducting question and answer sessions, and administering the post-test, the knowledge level increased from 74.6% to 90.6%.